Financial accountability and budgeting of waqf institution in Malaysia / Nathasa Mazna Ramli and Nurul Husna Mohd Salleh - Ramli, Nathasa Mazna; Mohd Salleh, Nurul Husna (UiTM Cawangan Johor, 2020)
This paper aims to explore the relationship of accounting and accountability for a waqf institution, where it addresses the manner in which accounting practices may aid in the achievement of accountability. Budgeting is believed to be a type of accounting practices undertaken to achieve accountability as it reflects an institution's annual financial planning. A single case study is used to meet the research objective. Focusing on a single waqf institution allows an in-depth exploration of budget practices and elements that may subsequently influence the practice. The findings show that accountability is positively understood by members of the organisation, as well as their responsibilities as a mutawalli in achieving the financial accountability. This research provides an insight into accountability perceptions which can impact accounting practices in waqf institutions.